Derajat Hipertensi dengan Kejadian Stroke Iskemik Berulang pada Pasien yang Dirawat di Rumah Sakit - Nur'ain Towalu; Muhammad Isman Jusuf; Ibrahim Suleman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the relationship between hypertension levels and the incidence of recurrent ischemic stroke in ischemic stroke patients at Dr. M.M. Dunda Limboto Regional General Hospital and Hasri Ainun Habibie Regional General Hospital. The method used was quantitative with an observational analytical design and a cross-sectional approach. The study population consisted of 225 ischemic stroke patients, with a sample of 70 respondents selected using a purposive sampling technique. Data were obtained from medical records using a checklist and analyzed using the Chi-Square test. The results showed that the majority of respondents experienced grade 3 hypertension (38 respondents (54.3%), and recurrent ischemic stroke (39 respondents (55.7%). Of the 39 respondents who experienced recurrent ischemic stroke, 28 respondents (71.8%) were in the grade 3 hypertension category. The Chi-Square test results showed a p-value of 0.001 (p<0.05), indicating a significant relationship between hypertension levels and the incidence of recurrent ischemic stroke. In conclusion, the higher the degree of hypertension, the greater the risk of recurrent ischemic stroke. Blood pressure control is necessary to prevent stroke recurrence. Keywords: Degree of Hypertension, Ischemic Stroke, Recurrent Ischemic Stroke